River Health Assessment Method Based on Water Quality Indices for the Dagujia River in China - Yi, Xuejun; Shi, Yuhao; Jiang, Long; Fu, Changlu; Xing, Yuzhen; Yu, Zhongjiang (Frontiers in Physics, 2022)
River health has become one of the major concerns today due to impacts of human activities. This study develops a water quality index index-based health assessment method to diagnose the status of the Dagujia River, China. The Dagujia River is the second largest river and the main source of drinking water in Yantai, China. The health status is classified into 5 levels - ideal, healthy, sub-healthy, unhealthy and morbid. The assessment process includes four phases: (1) index layer grading, (2) criterion layer grading, (3) target layer grading, and (4) health diagnosis. The results show that 8 sections of the river are morbid, accounting for 66.3% of the entire assessed river. It also finds that higher water temperature variation (WTV) is the main factor resultingresults in this poor health situation. However, the assessment excluding WTV reveals that all the other sections are in ideal states except for a sub-healthy river section that is caused by the higher concentrations of CODMn and COD in the high flood season(June-September).